Breaking the Bonds of Reciprocity in Negotiations - Brett, Jeanne M.; Shapiro, Debra L.; Lytle, Anne L. (Academy of Management Journal, 1998)
We tested hypotheses concerning the effectiveness of three strategies for breaking conflict spirals in negotiations. We also investigated the relationship between outcomes and the relative frequency of reciprocated contentious communications. Results confirmed the hypotheses, showing that extreme distributive outcomes are related to the relative frequency of reciprocated contentious communications and that conflict spirals can be stopped by various communication strategies. Theoretical and practical implications for managing contentious negotiations are discussed.